Pengaruh Cash Turnover dan Receivable Turnover terhadap Likuiditas pada Perusahaan Manufaktur - Mudjiyono, Mudjiyono; Krisnawati, Hani; Susilo, Bambang Widjanarko (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2021)
This study aims to examine the effect of receivable turn over and cash turn over and on the liquidity ratio in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The data collection technique used purposive sampling criteria technique. Companies that published financial reports consecutively during the 2016-2019 period. Data analysis is using multiple linear regression, simultaneous F test, hypothesis testing, classical assumption test. The results showed cash turn over had an effect on liquidity, receivable turnover had no effect on liquidity and simultaneously affected the liquidity ratio.